(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to demonstrate the impact of revenue recognition in installment sales contracts on the financial performance evaluation of companies operating in the field of installment sales contracts, through adherence to the international financial reporting standard IFRS15, revenue from contracts with customers, which leads to showing the real income result for each financial period, which represents a more reliable representation, and improves the company’s financial performance. The research reached a number of conclusions, perhaps the most important of which is that It is not possible to apply both (the installment sales method and the cost recovery method) when adopting the IFRS15 standard, and the first and second installments of the value of the housing unit and the cash sale amount that is received before performing the obligation by the company are considered contract obligations. Among the most important recommendations reached by the research included the need to apply the IFRS15 standard in companies operating in the field of installment sales to separate cash sales from installment sales. The IFRS15 standard must be applied in installment sales companies to help management determine the amount of expected future revenues, and the necessity of adopting the IFRS15 standard. To show the company’s actual performance for each year separately.